Input promotion within a complex subsector: Fertilizer in Nigeria - Liverpool-Tasie, Lenis Saweda O.; Takeshima, Hiroyuki (Wiley, 2013)
Despite growing evidence that fertilizers can substantially increase yields and slow down environmental degradation in sub‐Saharan Africa (SSA), the region still lags far behind other developing areas in fertilizer use. Low use rates persist despite numerous efforts to ease farmers’ access to quality and affordable fertilizer. This article reviews the effects of Nigeria's fertilizer policies, including fertilizer subsidies, on fertilizer use. We also compare the old government‐led fertilizer subsidy scheme with the more recent voucher‐based programs and their potential effects on private fertilizer sector development. Based on our analysis of Nigeria's experience with fertilizer subsidies, we identify the potential major challenges to be faced by the new fertilizer subsidy scheme currently being implemented nationwide.